Perception on Management of Nursing Education Institutes among Bachelors Students in Selected Nursing Colleges at Kathmandu - Dangol, Bhuwan Kumari; Thapa, Narbada (Journal of Advanced Academic Research, 2020)
Management is a process of planning, decision making, organizing, leading, motivating and controlling, and an effective utilization of the resources to reach the organizational goals efficiently and effectively. Management has a crucial role in quality of work and production in any institutions. Although a rapid increase of Nursing Education Institutions in Nepal since last decade which had been trained thousands of nursing cadres, the management aspects of these institutions are not studied adequately. Thus current study intended to explore the current status of Nursing Education Institution Management as experienced and perceived by the bachelors nursing students. A descriptive cross-sectional study was conducted among the nursing institutions in Kathmandu valley. Of the total 28 in the valley, 14 were selected purposively. From the selected institutions, all 377 eligible students currently in final year of study were selected. Among them, 208were from BSN and 169 were from B Sc program. The data was collected through the self administered structured questioners after taking informed consent. Data entry and analysis was done in SPSS version 16 software. The findings of the study show that 70% students were satisfied in institutional management (mean59.62, SD ± 3.66). In academic management (78%), (mean139.82, SD ± 6.22), followed by human resources 67%, (mean43.54, SD ± 2.79) and were in physical resources management 75% students were satisfied (mean45.02, SD ± 3.08). Analysis of variations between group (administrators, faculties, students) found statistical significance (p value <0.05). So it is concluded the perception of students, faculties and administrator were different on managing the nursing education.